Activation of h‐BN and SiC monolayer sheets through foreign atom substitution; a comparative study based on ab‐initio method. Issue 9 (15th August 2022) - Fatima, Kaneez; Rafique, Muhammad; Soomro, Amir Mahmood; Kumar, Mahesh
Abstract: Here, we studied two different 2D monolayer systems (i.e., h ‐BN and SiC), which exhibit unique electronic and magnetic properties. We analyzed the effects of Transition Methods (TM) doped atoms (i.e., Mn, Ni, and Sc) on the single vacancy (SV) h ‐BN and SiC systems using first principles calculations. Through comparison we found that Mn substitution in SV h ‐BN and SiC can modify their electronic and magnetic properties having larger magnetic moment as compared to other dopants (i.e., Ni and Sc.). Band structure and PDOS plots confirmed that TM doping in SV h‐ BN can convert the pure h ‐BN (insulator) to semiconductor, metal, or semi‐metal, it is also observed from the results that Mn‐doped h ‐BN has higher band gap approximately equal to Eg ~ 2.7 eV during the negative spin and has smaller band gap, that is, (Eg ~ 1.1 eV) during the positive spin. Similarly doping with the TM atoms on the SV SiC monolayer system can convert pure SiC to metal or half metal. In addition, Mn‐doped SiC showed semimetal property having 0 eV band gap. These finding will help us to vary the electronic and magnetic properties of the pure h ‐BN and SiC sheets which can be used for the opto‐electronic and spintronic applications. Abstract : In our present work, we develop two different 2D h ‐BN and SiC monolayer systems and theoretically analyze effects of Transition Metal (TM) as the impurity elements (i.e., Mn, Ni, and Sc) in the single vacancy (SV) h ‐BN and SiC monolayer systems using first principles calculations based on DFT technique. It is concluded from band structures and PDOS plots that, doping with TM elements in h ‐BN/SiC can effectively tune their electrical and magnetic properties. Furthermore, from the comparative analysis of TM‐doped (Mn, Ni, SC) in SV h ‐BN/SiC nanosheets, it is observed that Mn‐doped SiC monolayer system has semiconducting properties during negative spin and metallic properties during positive spin hence it has semi‐metallic properties in nature.